Hanbok in Art Fashion - Puspitasari, Feny; Khoirunnisa, Nida (Universitas Pendidikan Indonesia, 2021)
Hanbok is a traditional South Korean dress. Currently, Hanbok is only used on formal and semi-formal occasions such as weddings, festivals, or special Korean celebrations. This Korean Traditional Dress has a unique shape because it is a blend of Chinese and Japanese culture which is the identity of the Korean state. The designers are very creative in the appearance of the handbok in various looks, one of which is art fashion. The purpose of this work is to create an innovation in hanbok as art fashion with an autumn theme. The methods used product adaptation, with steps are creating a concept, mood board, making several alternative designs, and product prototyping. The result of the product in the form of color adaptation and maple leaves that are identical to autumn is applied to the development of hanbok, especially on jeogori. The response from respondents regarding Hanbok in art fashion is that the product has 2 dominant characteristics that are visible, namely 86% attractiveness, and 73% feminine. In addition, as many as 89% of respondents rate this product according to the characteristics of art fashion.